"An Invaluable Acquisition": Sandglasses in Romantic Literature. Issue 6 (2nd November 2017) - Tomalin, Marcus
ABSTRACT: The sandglasses that appear in the literature of the Romantic period were far more than outmoded remnants of the pre-industrial past. Although their medieval iconographical connotations persisted, they continued to serve pragmatic functions in important social rituals. They featured prominently in contemporaneous discourses about temporality, and their abiding cultural relevance is overtly manifest in many literary descriptions, metaphors, and allusions. This article explores such references before focusing specifically on philosophical contexts, and the writings of Coleridge in particular. His sandglass-based descriptions and analogies provide unexpectedly illuminating insights into the emergence of distinctively Romantic attitudes toward horology, the practicalities of time telling, atomism, and finitude. Although necessarily fragmentary, this article reveals, for the first time, the rich polysemic intricacy of the sandglasses that served so many different purposes in British Romantic literature.